Injectable hyaluronic acid hydrogel loaded with BMSC and NGF for traumatic brain injury treatment. (January 2022) - Wang, Luyu; Zhang, Dan; Ren, Yikun; Guo, Shen; Li, Jinrui; Ma, Shanshan; Yao, Minghao; Guan, Fangxia
Abstract: Injectable hydrogel has the advantage to fill the defective area and thereby shows promise as therapeutic implant or cell/drug delivery vehicle for tissue repair. In this study, an injectable hyaluronic acid hydrogel in situ dual-enzymatically cross-linked by galactose oxidase (GalOx) and horseradish peroxidase (HRP) was synthesized and optimized, and the therapeutic effect of this hydrogel encapsulated with bone mesenchymal stem cells (BMSC) and nerve growth factors (NGF) for traumatic brain injury (TBI) mice was investigated. Results from in vitro experiments showed that either tyramine-modified hyaluronic acid hydrogels (HT) or NGF loaded HT hydrogels (HT/NGF) possessed good biocompatibility. More importantly, the HT hydrogels loaded with BMSC and NGF could facilitate the survival and proliferation of endogenous neural cells probably by neurotrophic factors release and neuroinflammation regulation, and consequently improved the neurological function recovery and accelerated the repair process in a C57BL/6 TBI mice model. All these findings highlight that this injectable, BMSC and NGF-laden HT hydrogel has enormous potential for TBI and other tissue repair therapy. Graphical abstract: An injectable hyaluronic acid hydrogel loaded with BMSC and NGF accelerates the neurological function recovery of traumatic brain injury. Image 1